Noniterative multiplane holographic projection - Velez Zea, Alejandro (2020)
In this paper, we introduce a mixed complex and phase-only constraint for noniterative computer generation of phase-only holograms from multiplane intensity distributions. We are able to reproduce three-dimensional intensity distributions with the same number of planes achieved with the Gerchberg–Saxton (GS) algorithm; at the same time, we maintain the fast computation time of a noniterative method. In this way, we enable the possibility of multiplane light field control in dynamic applications. We show numerical results for three- and eight-plane holograms, for different interplane distances—using either the same or different amplitude constraints in each plane. In all of these tests, our method results in a comparable or better reconstruction quality than the GS algorithm, while achieving a significant decrease in computing time. Finally, we experimentally demonstrate the capability of our proposal to achieve multiplane holographic projection.